2022
DOI: 10.1002/chem.202103781
|View full text |Cite
|
Sign up to set email alerts
|

MOF‐Stabilized Perfluorinated Palladium Cages Catalyze the Additive‐Free Aerobic Oxidation of Aliphatic Alcohols to Acids

Abstract: Extremely high electrophilic metal complexes, composed by a metal cation and very electron poor σ‐donor ancillary ligands, are expected to be privileged catalysts for oxidation reactions in organic chemistry. However, their low lifetime prevents any use in catalysis. Here we show the synthesis of fluorinated pyridine‐Pd2+ coordinate cages within the channels of an anionic tridimensional metal‐organic framework (MOF), and their use as efficient metal catalysts for the aerobic oxidation of aliphatic alcohols to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 92 publications
0
11
0
Order By: Relevance
“…In particular, the fully fluorinated ligand, bis(2,3,5,6-tetrafluoro-pyridin-4-yl)acetylene (L 3 ), allows us to synthesise and precisely characterise by SCXRD a Pd II 6 square metal–organic polygon, which shows efficient catalytic behaviour in the aerobic oxidation of aliphatic alcohols to carboxylic acids without any additive. 114 This work nicely illustrated the dual role of MOFs as chemical nanoreactors, enabling the formation of SCCs, that in the homogenous phase could not be assembled due to the poor Sigma-donor ability of L 3 , and transferring the stability from the MOF to the assembled SCC, through weak supramolecular interactions, which make possible to fully take advantage of the electrophilic potential of palladium cations constituting the SCC.…”
Section: Mof-driven Self-assembly Of Sccsmentioning
confidence: 71%
“…In particular, the fully fluorinated ligand, bis(2,3,5,6-tetrafluoro-pyridin-4-yl)acetylene (L 3 ), allows us to synthesise and precisely characterise by SCXRD a Pd II 6 square metal–organic polygon, which shows efficient catalytic behaviour in the aerobic oxidation of aliphatic alcohols to carboxylic acids without any additive. 114 This work nicely illustrated the dual role of MOFs as chemical nanoreactors, enabling the formation of SCCs, that in the homogenous phase could not be assembled due to the poor Sigma-donor ability of L 3 , and transferring the stability from the MOF to the assembled SCC, through weak supramolecular interactions, which make possible to fully take advantage of the electrophilic potential of palladium cations constituting the SCC.…”
Section: Mof-driven Self-assembly Of Sccsmentioning
confidence: 71%
“…Due to the divergent feature of L 22 , reaction of it with Pd II gave polymeric products, as suggested by the extremely broadened NMR spectra. In their early report, combination of banana-shaped bidentate L 14 , L 21 with Pd II ions formed a heteropletic cis-[Pd 2 (L 14 ) 2 (L 21 ) 2 ] cage. [82] Given that L 22 and L 23 composed of a pair of L 14 covalently linked by flexible or rigid units, respectively, and the assembly of L 22 with L 21 or L 23 with L 21 was tested.…”
Section: Four Ligand Combinatorial Self-assemblymentioning
confidence: 99%
“…[82] Given that L 22 and L 23 composed of a pair of L 14 covalently linked by flexible or rigid units, respectively, and the assembly of L 22 with L 21 or L 23 with L 21 was tested. The results indicated that mixed-ligand assembly of L 22 and L 21 in CD 3 CN led to a heteroleptic twocavities [Pd 4 (L 21 ) 4 (L 22 ) 2 ] cage. In DMSO-d 6 , the same components afforded a [Pd 3 (L 21 ) 4 L 22 ] pseudo-tetrahedron.…”
Section: Four Ligand Combinatorial Self-assemblymentioning
confidence: 99%
See 2 more Smart Citations